In vitro unfermented fiber is a good predictor of the digestible and metabolizable energy content of corn distillers dried grains with solubles in growing pigs - Zeng, Zhikai (J Anim Sci, 2019)
Characterizing fiber into fermentable and unfermentable fractions may enhance the accuracy of estimating DE and ME energy content in fiber-rich ingredients. Therefore, the objective of this study was to analyze the concentrations of NDF, representing both the fermentable (fNDFom) and unfermentable (uNDFom) portions among sources of corn distillers dried grains with solubles (DDGS), and determine their relative contributions to DE and ME content. The concentrations of DE and ME, as well as apparent total tract digestibility (ATTD) of GE, were measured in a previous experiment. Samples of DDGS (0.5 g) were mixed with fecal inoculum and incubated for 8, 12, and 72 h. The ash corrected NDF (NDFom) content of DDGS residues at each time point was determined. The fNDFom increased with fermentation time of 8 h (21.6%), 12 h (29.0%), and 72 h (68.6%). The ATTD of GE increased as the uNDFom decreased at 8 h (uNDFom8; R(2) = 0.83; P < 0.01) and 72 h (uNDFom72; R(2) = 0.83; P < 0.01). Likewise, ME content of DDGS increased as uNDFom72 decreased (R(2) = 0.59; P < 0.01). The best-fit DE equation was DE (kcal/kg DM) = 2,175 – 3.07 × uNDFom8 (g/kg, DM) – 1.50 × uNDFom72 (g/kg, DM) + 0.55 × GE (kcal/kg DM) (R(2) = 0.94, SE = 36.21). The best-fit ME equation was ME (kcal/kg DM) = 1,643 – 2.31 × uNDFom8 (g/kg, DM) – 2.54 × uNDFom72 (g/kg, DM) + 0.65 × GE (kcal/kg DM) – 1.42 × crude protein (g/kg DM) (R(2) = 0.94, SE = 39.21). These results indicate that in vitro unfermented fiber is negatively associated with GE and NDF digestibility, and therefore, is a good predictor of DE and ME content in corn-DDGS.